Organic waste valorisation towards circular and sustainable biocomposites. Issue 14 (8th July 2022) - Lizundia, Erlantz; Luzi, Francesca; Puglia, Debora
Abstract : Organic waste valorisation into biopolymers and nanofillers potentially lowers the pressure on non-renewable resources, avoids the generation of waste-streams and opens new opportunities to develop multifunctional bio-based products. Abstract : The adoption of circular production and consumption patterns that counteract the current issues related to the depletion of natural resources, global warming, and environmental pollution is one of the most pressing global challenges that faces our society. Considering the potential of organic waste and residue streams to be transformed into valuable products, much effort is now being directed to foster circular bio-economy strategies. The valorisation of organic waste reduces the pressure on non-renewable resources and avoids the generation of waste. Organic waste valorisation has attracted much attention from fundamental and applied fields, given its wide availability and versatility. This review aims to provide an insight into valorisation of organic waste of aquatic, agricultural, forestry and animal origin to polymeric matrices, bionanoparticles and their combination. An introductory analysis dealing with state-of-the-art circular bioeconomy, recycling and upcycling is provided. Then, a literature review in the context of biopolymers and derived nanoparticles is provided, emphasizing toxicity and biodegradability aspects. The environmental impacts of valorisation processes are analyzed according to life cycle assessment. The establishment of organic waste conversion routes will lead to innovative bio-based industries, opening new market opportunities for bio-based products and achieving efficient resource utilisation. However, the social, economic and political barriers still encountered must be overcome.